PENGARUH SPORT MASSAGE TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA PENDERITA PRA-HIPERTENSI DAN HIPERTENSI DERAJAT 1 DI PANTI SOSIAL TRESNA WERDHA YOGYAKARTA UNIT ABIYOSO - Ignatius Djuniarto; Putu Kusumarini; Anida Anida (STIKES Wira Husada Yogyakarta, 2014)
ABSTRACTBackground: Unmitigated elevated Blood Pressure (BP), be it pre-hypertension or hypertension, results in dire health consequences. Approximately 25-46% of the world population suffers from pre-hypertension, while the prevalence of stage-1 hypertension has not been surveyed yet. Sport massage (back massage) can lower blood pressure in people with hypertension. Historically, massage has been an integral part of nursing care. Preliminary study at Panti Sosial Tresna Werdha (PSTW) Yogyakarta unit Abiyoso in June 2012 showed that from the total 126 residents, there were 38 people suffering from pre-hypertension and 26 people were on stage-1 hypertension.Objective: To identify the influence of sports massage in decreasing blood pressure suffered by the elderly with pre-hypertension and stage-1 hypertension in PSTW Yogyakarta unit Abiyoso. Method: In this quasy experimental, pretest-posttest study without control group, a 10-min back massage was given to the respondent (n = 30), three times a week for 10 sessions. The population was the residents of PSTW Yogyakarta unit Abiyoso. The BP was measured using digital tensimeter. The research was conducted in January 2013. The data was analyzed using t-test analysis.Results: There is a decrease in the number of patients with pre-hypertension after given massage by 6.7%, while a decrease in the number of patient with stage-1 hypertension by 20 %. Analysis of t-test determined systolic BP change significantly (t count = 6.271, p = .000) as did diastolic BP in elderly with pre-hypertension and stage-1 hypertension (t value = 3.079, p = .005).Conclusion: sport massage influences blood pressure reduction of the elderly with pre-hypertension and stage-1 hypertension in PSTW Yogyakarta unit Abiyoso.